Secrecy performance analysis of a IRS-assisted underwater optical wireless communication system - Dang, Tien Sy; Nguyen, Van Thang; Cao Van Toan; Dang, The Ngoc (Journal of Military Science and Technology, 2024)
In response to the dearth of radio frequency (RF) equivalents, there has been a recent surge in interest in optical wireless communication in underwater environments. To ensure a strong line-of-sight (LOS) connection, the intelligent reflecting surface (IRS) is installed to create a virtual LOS. Then, the first part of this study looks into the security of underwater optical wireless communication (UOWC) in relation to a number of real-world phenomena, including oceanic propagation loss, oceanic turbulence, and IRS-induced geometric loss. Then, a wiretap channel with three authorized users - a reputable broadcaster named Alice (the submarine), a law-abiding user named Bob, and an eavesdropper named Eve - is examined over turbulent channels that exhibit the Log-normal distribution. Furthermore, our study derives the closed-form formulas for the secrecy performance measures, secrecy outage probability, and secrecy throughput. Finally, the numerical results show how the impact of oceanic turbulence-induced fading and distance between Bob’s and Eve’s positions on the secrecy system performance.